Navigating the Labyrinth of Silence: Feminist Artists in Mexico - McCaughan, Ed (Social justice, 2007)
Part of a special issue on the relationship between art, identity, and social justice. The writer explores some of the mechanisms and practices through which women artists are excluded from the mainstream and their responses to such exclusion. He focuses on the feminist artists who participated in the feminist movement and the grupos movement of art collectives in Mexico in the 1970s. He finds that, in each of these arenas, feminist artists encountered numerous obstacles to full creative expression, participation, and recognition. He also observes that feminist artists often created their own alternative spaces, including formal discussion groups, formal feminist art collectives, collaborative art projects, group shows, and the establishment of new galleries and cultural spaces. He suggests that these artists have since had some success in penetrating the overwhelmingly male world of art spaces.